Preoperative Patient-Reported Outcomes Measurement Information System Global Health Scores Predict Patients Achieving the Minimal Clinically Important Difference in the Early Postoperative Time Period After Total Knee Arthroplasty. Issue 24 (15th December 2021) - Darrith, Brian; Khalil, Lafi S.; Franovic, Sreten; Bazydlo, Michael; Weir, Robb M.; Banka, Trevor R.; Davis, Jason J.
Abstract : Introduction: The patient-specific factors influencing postoperative improvement after total knee arthroplasty (TKA) are important considerations for the surgeon and patient. The primary purpose of this study was to determine which patient demographic factors influence the postoperative Patient-Reported Outcomes Measurement Information System (PROMIS) Global Health (GH) scores. In addition, we aimed to compare the prognostic utility of preoperative PROMIS-GH scores and the Knee Injury and Osteoarthritis Outcome Score for Joint Replacement (KOOS-JR) in predicting postoperative improvement. Methods: This retrospective cohort study of a consecutive series of patients who underwent primary, unilateral TKA analyzed prospectively collected KOOS-JR and PROMIS-GH surveys. PROMIS-GH includes physical health (PH) and mental health scores. Patient demographic and presurgical characteristics were evaluated for prognostic capability in predicting postoperative improvement in the PROMIS scores and achievement of the minimal clinically important difference (MCID). Receiver operating characteristic curves were used to understand the prognostic thresholds of the preoperative PROMIS score and KOOS-JR for predicting MCID achievement. Results: A total of 872 patients were included. Although unadjusted analyses showed associations between patient demographic factors and PROMIS-PH scores, multivariable regression analysis for predictors of MCID achievement demonstrated that PROMIS-PH was the only significant preoperative variable. Receiver operating characteristic analysis revealed that the area under the curve of PROMIS-PH (0.70; 95% CI, 0.67 to 0.74) was less than that of the KOOS-JR (0.77; 95% CI, 0.73 to 0.81; P = 0.032). Sensitivity and specificity for achieving the MCID were maximized for preoperative PROMIS-PH scores of ⩽ 38 (59% and 70%) and for preoperative KOOS-JR ⩽ 51 (71% and 69%). Conclusions: Preoperative KOOS-JR and PROMIS-PH scores predict clinically meaningful improvement after TKA. The KOOS-JR has greater prognostic utility in the early postoperative period. Level of Evidence: Level III, Prognostic Study